1986
DOI: 10.1029/wr022i010p01385
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Gamma Autoregressive Processes for Operational Hydrology

Abstract: A number of models have been suggested •or hydrologic time series in general and streamflow series in particular. Most of them are normal autoregressive (AR) of order 1 with either constant or periodic parameters. Since generally hydrologic time series are nonnormal (skewed), transformations have been suggested to make the series approximately normal. A new class of univariate models is proposed herein which incorporates skewed and correlation properties within the model structure without the necessity of tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
44

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 33 publications
0
44
0
44
Order By: Relevance
“…Nevertheless, it is noteworthy that Song et al [45] and Jeong and Lee [46] also observed this issue independently while studying AR(1) with exponential white noise [47][48][49] and periodic Gamma autoregressive (PGAR) processes [50], respectively. However, to the best of our knowledge, these works, or any other, have not revealed the envelope limitation, neither provided a theoretical proof and a justification for this behavior, which probably arises from the lack of explicit assumption regarding the joint dependence structure of the process.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is noteworthy that Song et al [45] and Jeong and Lee [46] also observed this issue independently while studying AR(1) with exponential white noise [47][48][49] and periodic Gamma autoregressive (PGAR) processes [50], respectively. However, to the best of our knowledge, these works, or any other, have not revealed the envelope limitation, neither provided a theoretical proof and a justification for this behavior, which probably arises from the lack of explicit assumption regarding the joint dependence structure of the process.…”
Section: Discussionmentioning
confidence: 99%
“…Classical nonlinear approaches typically require large amounts of exogenous information, which is not always available (Deo and Thirumalaiah, 2000). Some nonlinear and non-Gaussian techniques do not need exogenous information and behave better than linear models, as in the case of periodic gamma autoregressive processes PGAR (Fernandez and Salas, 1986), but they are univariate models. Different authors (Lapedes and Farber, 1988;Tang et al, 1991;Zealand et al, 1999;Imrie et al, 2000;and Salas et al, 2000) have tested the capability of certain NN topologies to incorporate complex and non-linear hydrological relationships; they remark on their potentials and abilities as tools for hydrological forecasting.…”
Section: Fig 1 Location Of Entrepeñas and Buendía Reservoirs In Thementioning
confidence: 99%
“…This comparison is the right way to validate a model if it is intended for water resources systems planning and management management and planning (Jackson, 1975;Salas et al, 1980;Stedinger and Taylor, 1982;Fernandez and Salas, 1986;Kendal and Dracup, 1991;Basson and van Rooyen, 2001). Therefore, considering that the proposed model is not a forecasting approach, the performance of the NN-based model must not be evaluated by using the classical procedure of splitting all available data into training and validation (and/or) test sets.…”
Section: Evaluation Of Models' Performancementioning
confidence: 99%
“…However, using the mixture scheme given above, this four-parameter second-order process can be extended to higherorders quite simply (Lawrance and Lewis, 1985a Fernandez and Salas (1985) have extended the autoregressive Gamma process to the case of periodic parameters; this is an extension to the nonGaussian case of the so-called "Thomas-Fiering model", although the model is actually due to Hannan (1955).…”
Section: Higher-order Autoregressive Processesmentioning
confidence: 99%